Der Begriff der Verständlichkeit in der modernen Physik (1948). (June 2016) - Feyerabend, Paul K.
Abstract: This is a critical transcription of Paul Feyerabend's earliest extant essay "Der Begriff der Verständlichkeit in der modernen Physik" (1948) recovered from the European Forum Alpbach archives. In it, Feyerabend defends positivism as a progressive framework for scientific research in certain stages of scientific development. He argues that in physics visualizability ( Anschaulichkeit ) and intelligibility ( Verständlichkeit ) are time-conditioned concepts: what is deemed visualizable in the development of physical theories is relative to a specific historical context and changes over time. He concludes that from time to time the abandonment of visualizability is crucial for progress in physics, as it is conducive to major theory change, illustrating the point on the basis of advances in atomic theory.